2021
DOI: 10.3390/ijerph182312293
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening in Semi-Rural Malaysia: Utilisation and Barriers

Abstract: Breast cancer (BC) is the commonest cancer in Malaysia. Delayed diagnosis is a significant cause of BC mortality in the country. Early diagnosis and screening are vital strategies in mortality reduction. This study assessed the level of utilisation and barriers for breast self-examination (BSE), clinical breast examination (CBE) and mammogram in a semi-rural population in Malaysia and compared these across the different ethnic groups. This cross-sectional study was conducted among women aged 40 years and above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Furthermore, women's financial concerns also opposed the reduction in subsidised mammogram available each month. This is in line with previous research suggesting 70% of women see cost as a barrier to screening [14]. These issues highlight the conflicting reality between women's personal barriers that are exacerbated by the shortcomings in the healthcare system that have been highlighted in this study [31].…”
Section: Plos Onesupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, women's financial concerns also opposed the reduction in subsidised mammogram available each month. This is in line with previous research suggesting 70% of women see cost as a barrier to screening [14]. These issues highlight the conflicting reality between women's personal barriers that are exacerbated by the shortcomings in the healthcare system that have been highlighted in this study [31].…”
Section: Plos Onesupporting
confidence: 91%
“…nurses and radiographers). This was similar to quantitative findings reported previously where 50% women from Segamat reported that male doctors pose a barrier to BC screening attendance [14]. Since BC screening has to be conducted by female radiographers in Malaysia, this likely leads to underuse of mammogram facilities.…”
Section: Plos Onesupporting
confidence: 87%
See 2 more Smart Citations
“…In other words, a significant proportion of older women at risk of BC appear to have been missed. Moreover, screening uptake varied according to availability of screening facilities, and implementation is challenging in terms of difficulties related to accessing services, especially in rural areas (Htay et al, 2021; Mohan et al, 2021).…”
Section: Cancer Screening Programme Provision and Uptakementioning
confidence: 99%